(untitled) (Philologia, 2023)
The role of aspiration (positive VOT) in English and Serbian differs significantly. While positive VOT helps distinguish between voiced and voiceless plosives in English, it has no distinctive function in Serbian. For this reason, a clear contrast between long-lag stops of English and short-lag stops of Serbian might prove challenging for Serbian EFL students. For this reason, this paper examines the degree of aspiration in initial voiceless stops in both Serbian and English with two separate target groups: five intermediate and five highly proficient speakers of English. The aim of this study is to determine to what extent L1 affects L2 speech and how this is reflected in the two groups of speakers. All participants are asked to read sentences containing target words with voiceless stops in initial position while being recorded with the help of Praat (Boersma/Weenink, 2022). For every token, we measure VOT for the interval between the release of the plosive and the onset of voicing of the following sound, expressed in milliseconds (ms). The results show that more proficient EFL speakers reach native-like VOT values. This experiment, however, yielded some striking results, specifically the proof of significant L2 transfer, where the same proficient speakers pronounce their stops with a significant degree of aspiration in Serbian, which deviates from the phonetic habits of native speakers of Serbian. Results also show that, even though the use of long-lag stops in intermediate users does not resemble that of native speakers, they make a clearer distinction when it comes to applying VOT in their L1 and L2 respectively.